LINGUOPOETIC FEATURES OF PHONOLOGICAL PARALLELISM IN AZERBAIJAN AND ENGLISH - G.R ABBASOVA (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
The article deals with possible ways of creating phonological parallelism in the Azerbaijan and English languages. It analyzes how similar and different ways are possible in these languages. On the other hand, there has recently been a strong focus in historical linguistics on the development of quantitative methods for comparing and classifying languages and these have tended to be applied to problems of the languages such as Azerbaijani and English that have different typological structure. In spite of the possible differences of both languages sound patterning, rhythm and alliteration are noted as the main types of phonological parallelism. In the article these types of phonological parallelism have been illustrated with poetical samples of the stated languages. In order to learn linguopoetic features of phonological parallelism literary texts concerning on the types of phonological parallelism have been widely investigated. In Azerbaijani and English sound patterning is one of the main ways of forming phonological parallelism. In both languages sound pattering serves to create phonological parallelism that is formed by means of the repetition of similar sounds as in alliteration, assonance and rhythm. Sound patterning is considered as the use of sounds in syllables in words which are close enough to be one another in space or time to be perceived by readers or listeners. So, it has the features of creating and strengthening phonological parallelism. These features aid to find out types of sound patterning and their use by means of investigating phonological parallelism in both languages. Rhythm and alliteration also play crucial roles in the research of phonological parallelism. Both of them have been analyzed by means of poetic samples belonging to stated languages. In this article, we outline our attempts to address the question of the differences and similarities of rhythm and alliteration in both languages using quantitative methods.